Social Development - Christian Reutlinger; Hans Günther Homfeldt (Social Work and Society)
Numerous models have been formulated to describe development. Generally, these start off with a state of not-yet development or nondevelopment, and then go on to contrast this with a second state: some kind of plan or blueprint for development. As a result, the process of development is equated with a series of completed stages. Like having to climb the rungs of a ladder, one moves up and up in order to become more and more developed. The associated catching-up processes are then frequently described with phase models. ln contrast to such goal-directed perspectives on development with their links to modernization theory, social development pursues an alternative approach focusing on the empowerment and autonomy of actors, and also taking account of the structural obstacles that confront them as they shape their daily lives in the sense of learning to develop their selves. This means that development is always conceived within a twin framework of self- and other-development. Social development represents a holistic approach that is non-static and process-oriented.